KEHIDUPAN SOSIAL EKONOMI PETANI KELAPA DESA RAKU KECAMATAN TABUKAN UTARA KABUPATEN KEPULAUAN SANGIHE - Reylando G. H. Sembihingan (HOLISTIK, Journal of Social and Culture, 2023)
One of the characteristics of rural communities working to make a living in meeting their needs, namely in the agricultural sector. The village is said to be an agricultural village because the majority of the people grow crops. Agriculture is the basic livelihood of most people in rural areas which has an important role for their lives. Although there are villagers who do not work as farmers, such as carpenters, building coolies, merchants and other jobs, the villagers will refer to themselves as farmers. However, some villagers work in the agricultural sector. Farmers are a group of people who are found in various places in rural areas. They are people who live off the cultivation business by utilizing the resources provided by nature. His agricultural products or some of them will be produced to meet his household needs and the rest will be marketed to earn money that is used to buy various other household needs. Raku Village is a village that has the potential for natural resources that are quite abundant so that this village is also a mainstay of productivity in agriculture, relying on annual crops such as coconut, cloves and nutmeg and there are also other livelihoods such as fishermen and small shops (warungs). At first glance, if you look at some of these results, it will actually promise a future for the farming community in Raku Village. However, when viewed from improving the lives of the Raku Coconut Farmers community, they have not fully enjoyed the mainstay results of this potential. Raku Village coconut farmers produce agricultural products to meet their daily needs. Farmers' incomes are currently a very serious problem because the income earned by farmers is always changing due to various factors including weather and market conditions. Keywords : life, coconut farmer, income